A Postdramatic Engagement with Robinsonade Motifs in Tim Crouch’s I, Caliban - Özmen, Özlem (Porównania, 2019)
Tim Crouch’s I, Caliban is a postdramatic adaptation of Shakespeare’s The Tempest included in a collection titled I, Shakespeare in which he recreates Shakespeare’s most marginalised characters. The focus in this sequel adaptation is on Caliban who tries to survive after Prospero and all others have left the island. Different from the representation of Caliban in postcolonial reworkings of Shakespeare’s play, Caliban, in this work, is not preoccupied with taking revenge. Instead, he emphasises the need for social interaction as he has been left alone on his island. Drawing on former structural comparisons of The Tempest and Daniel Defoe’s Robinson Crusoe based on their common themes such as the island setting, master-servant relationship, colonial expansion, and power politics, the aim of this paper is to discuss Crouch’s adaptation as a transformation of common motifs of the Robinsonade in its attempt to respond to the ideological formations of Shakespeare’s text. Among such transformations, the concept of survival, for instance, is handled from the native’s viewpoint in Crouch’s work. Instead of the figure of the stranger who finds life on an unknown land difficult to cope with, this time, the native turns into a captive on the island though it is a familiar setting. Another motif used in an alternative manner is isolation, which is not presented as fuel for civilisation but as Caliban’s psychological trauma, which he explores through storytelling as a postdramatic element. Apart from the narration, the play demonstrates other uses of postdramatic elements to suggest an isolated figure on an uninhabited island like the use of objects such as toy boats and tape of sea sounds. Instead of seeing Crouch’s work as a postcolonial response to Shakespeare’s work, this paper will try to investigate how the use of island setting and the theme of isolation can make it closer to a Robinsonade. By this means, it will also try to ask whether an adaptation could also be read in relation to a work that is not intended as its source text.